Before and after knowledge management initiatives : after action review - Maruthaveeran, Vijayaletchumy (Persatuan Pustakawan Malaysia, 2012)
Implementation of a knowledge management (KM) project in an organization requires a strategy that is unique and exclusive. After Action Review (AAR) is a valuable strategy that is highly useful and appropriate to be conducted in line with other KM strategies. Refusal in implementing AAR would likely result in a negative impact. In this paper, the significance and method of implementing AAR are explained. The AAR process should be conducted at the end of a project and should be used as a guideline for new teams that are about to embark on various projects.